A review of the brittle ice zone in polar ice cores. Issue 68 (2014) - Neff, Peter D.
Abstract: Maintaining ice-core quality through the brittle ice zone (BIZ) remains challenging for polar ice-core studies. At depth, increasing ice overburden pressurizes trapped air bubbles, causing fracture of cores upon exposure to atmospheric pressure. Fractured ice cores degrade analyses, reducing resolution and causing contamination. BIZ encounters at 18 sites across the Greenland, West and East Antarctic ice sheets are documented. The BIZ begins at a mean depth of 545 ± 162 m (1 standard deviation), extending to depths where ductile clathrate ice is reached: an average of 1132 ± 178 m depth. Ice ages in this zone vary with snow accumulation rate and ice thickness, beginning as young as 2 ka BP at Dye-3, Greenland, affecting ice >160 ka BP in age at Taylor Dome, Antarctica, and compromising up to 90% of retrieved samples at intermediate-depth sites. Effects of pressure and temperature on the BIZ are explored using modeled firn-column overburden pressure and borehole temperatures, revealing complex associations between firn densification and BIZ depth, and qualitatively supporting expected thinning of the BIZ at low ice temperatures due to shallower clathrate stability. Mitigating techniques for drilling, transport, sampling and analysis of brittle ice cores are also discussed.